ANALISA PENERIMAAN SISWA TERHADAP G-CLASS ROOM PADA MASA PSBB COVID-19 MENGUNAKAN PENDEKATAN PLS-SEM - Andi Arfian (LPPM UNIVERSITAS BINA INSAN, 2020)
Currently, Large-Scale Social Restrictions (PSBB) are still being implemented to reduce the spread of COVID-19 in Indonesia. As a result of these restrictions the conventional education system has turned online and many students have had to adapt to this pandemic situation. The challenge of learning online is that a good internet connection will create good concentration and value for students. This study is an attempt to examine the factors that influence student acceptance of the Google Class Room in the learning process during the PSBB period at Smkn 5 Bekasi city. The Technology Acceptance Model (TAM) was adopted to formulate the current research hypothesis. Data were collected through an online questionnaire with 100 respondents. The Partial Least Square-Structural Equation Model (PLS-SEM) approach is used to assess measurements and structural models. The results prove that both perceived ease of use (PEOU) and perceived usefulness (PU) have a positive effect on intentional behavior and affect the actual use of the Google Class Room. From the positive results, this study concludes that the use of e learning technology using the method above has a very big influence on students in the learning process during the PSBB period. Keywords: Psbb, Tam, Sem-Pls